Analisis Kinerja Keuangan pada PT. Bank Pembiayaan Rakyat Syariah Bahari Berkesan Kota Ternate - Najla Syifa Y. Ichsan; Abdul Hadi Sirat; Irfan Zamzam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the financial performance of PT. BPRS Bahari Berkesan in 2019-2023. This research is a quantitative study. The data collection technique used is the documentation technique, namely the form of secondary data which searches for, records, and collects data. The type of data used is secondary data obtained from the annual financial report of BPRS Bahari Berkesan, Ternate City for the period 2019-2023. The analysis method uses the REC/RGEC approach. The results of the study indicate that the financial performance of BPRS Bahari Berkesan is categorized as healthy with a note, because there is a liquidity risk that needs to be fixed immediately. The results of the risk profit calculation, namely Non-Performing Financing (NPF) are in the